A política de saúde no governo Lula The health policy in Lula's government - Telma Maria Gonçalves Menicucci (Universidade de São Paulo, 2011)
O ensaio faz uma reflexão sobre a política de saúde nos oito anos de governo do Presidente Lula, identificando-se uma mudança de foco na agenda governamental, passando-se da ênfase exclusiva na implementação gradativa do SUS no primeiro mandato para as condições de vida e os determinantes da saúde no segundo, bem como de sua articulação com o desenvolvimento. Considera-se que políticas de saúde de um governo não podem ser avaliadas apenas setorialmente, sendo necessário examinar passos, traços e produtos do governo que têm repercussões na saúde da população e na organização do sistema de serviços. O argumento central é que o governo Lula foi mais inovador na sua atuação sobre os condicionantes da saúde do que no aspecto endógeno da política de saúde; no âmbito setorial, os avanços foram incrementais e qualitativos, no processo contínuo e difícil de implantação dos princípios do SUS em um contexto de despolitização da questão da saúde e de um debate restrito ao financiamento sem que sejam colocados na agenda pública os problemas estruturais do sistema de saúde. The essay reflects on the health policy implemented in the eight years of President Lula's government, identifying a change of focus in the governmental agenda: from the exclusive emphasis on the gradual implementation of SUS (Brazil's National Health System) in the first term of office to life conditions and health determinants in the second one. It argues that the health policies of a government cannot be evaluated only by a sectorial perspective; it is necessary to examine the government's steps, orientations and products that have repercussions on the population's health and on the organization of the services system. The central proposition is that Lula's government was more innovative concerning interventions on health determinants than regarding the endogenous aspect of the health policy. In the sectorial scope, the progresses were incremental and qualitative, in the continuous and difficult process of implementing the principles of SUS in a context of depoliticization of the health issue and of a debate focusing only on financing, without including in the public agenda the structural problems of the health system.